Prospective Comparison of Whole-Blood- and Plasma-Based Hepatitis C Virus RNA Detection Systems: Improved Detection Using Whole Blood as the Source of Viral RNA - Stapleton, Jack T. (American Society for Microbiology, 1999)
We previously demonstrated that whole blood contains significantly more hepatitis C virus (HCV) RNA than plasma. To validate the whole-blood-based HCV RNA detection method, a prospective comparison of HCV RNA detection in whole blood and plasma from 50 patients with chronic liver disease was undertaken. Whole-blood and plasma aliquots were independently tested for HCV RNA by reverse transcriptase (RT) PCR assay, and plasma was tested by the Roche Amplicor assay. HCV RNA was detected in 35 of 50 (70%) whole-blood samples by RT-PCR but in only 26 of 50 (52%) plasma samples tested by the Amplicor assay (P < 0.01). HCV RNA was detected in 85% of HCV antibody-positive patients by the whole-blood method compared with 74% of plasma samples by the Amplicor method. The five HCV antibody-positive subjects who were negative by whole-blood-based RT-PCR assay were all receiving interferon therapy and had normal transaminases at the time of testing. HCV RNA was detected in 38% of HCV antibody-negative subjects by the whole-blood-based RT-PCR assay compared with 6.25% of these patients by the Amplicor assay (P < 0.05). There were nine samples in which HCV RNA was detected in whole blood but the Amplicor test was negative. Eight of the nine RNAs prepared from these whole-blood samples tested positive in the Amplicor assay, thus confirming the specificity of our results. This study demonstrates that whole-blood-based HCV RNA detection is more sensitive than currently available commercial tests and that whole-blood RNA is suitable for use in commercial assays.